KARDIOCHIRURGIA DOROSŁYCHTreatment of permanent pacing infective complications in the reference centre. Necessary cooperation of the cardiologist and cardiac surgeon - Kutarski, Andrzej; Czajkowski, Marek; Jendrej, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Some technical and organisational aspects of removal of infected pacemaker systems are presented in the experience of the reference centre for management of electrotherapy complications. The cardiac surgeon’s role has evolved from single-person whole system extractor, to an important member of an interdisciplinary team for less invasive comprehensive treatment of complications. The present-day main role of the cardiac surgeon is readiness to prevent disaster caused by percutaneous lead extraction complications. In rare, precisely defined cases of lead extraction scheduled for open-chest surgery, the operation should be preceded by coronarography (excluding young patients) and removal of pacemaker, liberation of proximal part of leads and introduction of pocket suction drainage on the day before and outside the operating suite.